Electrocortical Activity in Older Adults Is More Influenced by Cognitive Task Complexity Than Concurrent Walking - Vila-Chã, Carolina; Vaz, Cláudia; Oliveira, Anderson Souza (Frontiers in Aging Neuroscience, 2022)
Human cognitive-motor performance largely depends on how brain resources are allocated during simultaneous tasks. Nonetheless, little is known regarding the age-related changes in electrocortical activity when dual-task during walking presents higher complexity levels. Thus, the aim of this study was to investigate whether there are distinct changes in walking performance and electrocortical activation between young and older adults performing simple and complex upper limb response time tasks. Young (23±3 years, n = 21) and older adults (69±5 years, n = 19) were asked to respond as fast as possible to a single stimuli or a double stimuli appearing on a touch screen during standing and walking. Response time, step frequency, step frequency variability and electroencephalographic (EEG) N200 and P300 amplitudes and latencies from frontal central and parietal brain regions were recorded. The results demonstrated that older adults were 24% slower to respond to double stimuli, whereas younger adults are only 12% slower (p<0.01). The longer response time for older adults was accompanied by greater step frequency variability following double-stimuli presentations (p<0.01). Older adults presented reduced N200 and P300 amplitudes compared to younger participants across all conditions (p<0.001), without influences of posture (standing vs walking) was found for both groups (p>0.05). More importantly, the P300 amplitude was significantly reduced for older adults when responding to double stimuli regardless of standing or walking tasks (p<0.05), with no changes in younger participants. Therefore, older adults can attenuate potential walking deficits experienced during dual-task walking in simple cognitive tasks. However, cognitive tasks involving decision making influence electrocortical activation due to reduced cognitive resources to cope with the task demands.